2022
DOI: 10.3389/fevo.2022.814966
|View full text |Cite|
|
Sign up to set email alerts
|

Distribution, Status, and Conservation of the Indian Peninsular Wolf

Abstract: An understanding of the distribution range and status of a species is paramount for its conservation. We used photo captures from 26,838 camera traps deployed over 121,337 km2 along with data from radio-telemetry, published, and authenticated wolf sightings to infer wolf locations. A total of 3,324 presence locations were obtained and after accounting for spatial redundancy 574 locations were used for modeling in maximum entropy framework (MaxEnt) with ecologically relevant covariates to infer potentially occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In high-income regions, such as most North American states, human activities and large carnivores are frequently spatially separated, and most people involved in conflicts are those (a) visiting natural areas for recreational purposes [ 7 , 9 , 36 , 49 ]; or (b) living in urban and nearby landscapes, where potentially dangerous species may approach houses or inner-city parks, e.g., because they are involuntary attracted by anthropogenic food, or voluntarily fed [ 9 , 50 ]. In contrast, in lower-income countries, a greater portion of the human population live and work in rural areas where human and large carnivore habitat and activities overlap [ 18 , 40 , 51 ] (see also S1 File and S1 Table for more details on attack circumstances per species and region).…”
Section: Resultsmentioning
confidence: 99%
“…In high-income regions, such as most North American states, human activities and large carnivores are frequently spatially separated, and most people involved in conflicts are those (a) visiting natural areas for recreational purposes [ 7 , 9 , 36 , 49 ]; or (b) living in urban and nearby landscapes, where potentially dangerous species may approach houses or inner-city parks, e.g., because they are involuntary attracted by anthropogenic food, or voluntarily fed [ 9 , 50 ]. In contrast, in lower-income countries, a greater portion of the human population live and work in rural areas where human and large carnivore habitat and activities overlap [ 18 , 40 , 51 ] (see also S1 File and S1 Table for more details on attack circumstances per species and region).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in human population, habitat degradation, changing land use patterns, and low wild prey abundance have decreased the former range of wolves and even caused its local extinction (Jhala, 2003). In addition, the expansion of agricultural activities into marginal areas, including open plains, resulted in habitat loss and reduced their geographic range drastically (Mech, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of earlier wolf populations, wolf ecology, and their habitat assessment were primarily based on surveys and local-level information from pastoralists (Jhala & Giles 1991;Kumar & Rahmani 1997). A recent study using camera traps and a review of literature have suggested the presence of 3,170 Grey Wolves across the Indian subcontinent (Jhala et al 2022). The number of Indian Peninsular Wolves in the wild is equivalent to that of the royal Bengal Tigers Panthera tigris making it an Endangered species (Azad 2022).…”
Section: Introductionmentioning
confidence: 99%